THE CORRELATION OF PLAYING ROLE-PLAYING GAMES AND STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT - Praditya Putra (Journal of English and Education, 2014)
This research investigates the correlation of playing Role-Playing Games and students’ reading comprehension of narrative text. Thirty (30) ninth grade students who play Role-Playing Games participated in this study. Their frequency in playing Role-Playing Games and their ability in reading comprehension of narrative text are analyzed by using correlation research design. Correlation research design was used in this study in order to find out the tendency of relation between students’ frequency in playing role-playing game and their reading comprehension in narrative text. Creswell (2012, p. 338) states that correlation is a statistical test to determine the tendency or pattern between two variables or two sets of data to vary consistently. The result shows that the correlation degree between both variables is at the point of 0.687. It can be categorized as positive strong relationship, which means that students who play Role-Playing Games have a tendency to get higher score in reading comprehension of narrative text. From the findings, it is recommended that Role-Playing Games can be used as a media to teach narrative text to the students.